THE MISSION OF ALEKSANDAR BELIĆ AND STANOJE STANOJEVIĆ IN RUSSIA 1916–1917. (Heritage, 2023)
In the spring of 1916, the Serbian Government in exile sent two prominent intellectuals, the philologist Aleksandar Belić and the historian Stanojе Stanojević, on a propaganda mission to Russia, in order to inform the local public about its war aims and its national program. Serbian propaganda activity in Russia became much more organized after their arrival. During 1916, they worked on publishing books and establishing a Serbian institute in St. Petersburg, gave university and public lectures, met with members of the Duma and other influential politicians. Although there were some disagreements between Belić and Stanojević and the representatives of the Yugoslav Committee in Russia (mainly regarding the vision of the future unification), they generally cooperated well, especially in propaganda among Serb, Croat and Slovene volunteers in Odessa. The position of the Serbian representatives in Russia was fundamentally changed by the February Revolution. While liberal politicians were still influential, Belić and Stanojević made use of their acquaintances with them to get promises regarding the Serbian war aims. Their moderate optimism soon turned into bleak pessimism, because chaos and preoccupation with internal issues kept hindering Serbian propaganda in Russia. They tried to organize joint propaganda with Czechoslovak leader Tomáš Masaryk, but without much success. Stanojević left Russia in the summer, and Belić in the fall of 1917. They informed the Serbian Government that further propaganda in Russia was almost impossible. The initially fruitful mission of two Serbian intellectuals ended abruptly due to unpredictable events.
Keywords: First World War, Serbia, Russia, intellectuals, propaganda, Aleksandar Belić, Stanoje Stanojević, Russian Revolution